AkrinorTM, a Cafedrine/ Theodrenaline Mixture (20:1), Increases Force of Contraction of Human Atrial Myocardium But Does Not Constrict Internal Mammary Artery In Vitro - Kloth, Benjamin; Pecha, Simon; Moritz, Eileen; Schneeberger, Yvonne; Söhren, Klaus-Dieter; Schwedhelm, Edzard; Reichenspurner, Hermann; Eschenhagen, Thomas; Böger, Rainer H.; Christ, Torsten; Stehr, Sebastian N. (Frontiers in Pharmacology, 2017)
Background: Intraoperative hypotension is a common problem and direct or indirect sympathomimetic drugs are frequently needed to stabilize blood pressure. AkrinorTM consists of the direct and the indirect sympathomimetic noradrenaline and norephedrine. Both substances are covalently bound to the phosphodiesterase (PDE) inhibitor theophylline, yielding theodrenaline and cafedrine, respectively. We investigated pharmacodynamic effects of AkrinorTM and its constituents on contractile force and tension in human atrial trabeculae and internal A. mammaria rings. Methods: Isometric contractions were measured in human atrial trabeculae at 1 Hz and 37 °C. CGP 20712A and ICI 118,551 were used to elaborate β1- and β2-adrenoceptor (AR) subtypes involved and phenoxybenzamine to estimate indirect sympathomimetic action. PDE-inhibition was measured as a potentiation of force increase upon direct activation of adenylyl cyclase by forskolin. Human A. mammaria preparations were used to estimate intrinsic vasoconstriction and impact on the noradrenaline-induced vasoconstriction. Results: Clinically relevant concentrations of AkrinorTM (4.2 - 420 mg/l) robustly increased force in human atrial trabeculae (EC50 41±3 mg/l). This direct sympathomimetic action was mediated via β1-AR and the effect size was as large as with high concentrations of calcium. Only the highest and clinically irrelevant concentration of AkrinorTM increased the potency of forskolin to a minor extent. Norephedrine has lost its indirect sympathomimetic effect when bound to theophylline. Increasing concentrations of AkrinorTM (4.2 - 168 mg/l) alone did not affect the tension of human A. mammaria interna rings, but shifted the noradrenaline curve rightward from -logEC50 6.18±0.08 to 5.23±0.05 M. Conclusions: AkrinorTM increased cardiac contractile force by direct sympathomimetic actions and PDE inhibition, did not constrict A. mammaria preparations, but shifted the concentration-response curve to the right, compatible with an α-AR antagonistic effect or PDE inhibition. The pharmacodynamic profile and potency of AkrinorTM differs from noradrenaline and norephedrine in vitro. We anticipate metabolism of theodrenaline and cafedrine resulting in a different pharmacodynamic profile of AkrinorTM in vivo.